2022
DOI: 10.1093/plcell/koac242
|View full text |Cite
|
Sign up to set email alerts
|

MCU proteins dominate in vivo mitochondrial Ca2+ uptake in Arabidopsis roots

Abstract: Ca2+ signaling is central to plant development and acclimation. While Ca2+-responsive proteins have been investigated intensely in plants, only a few Ca2+-permeable channels have been identified, and our understanding of how intracellular Ca2+ fluxes are facilitated remains limited. Arabidopsis thaliana homologues of the mammalian channel-forming mitochondrial calcium uniporter (MCU) protein showed Ca2+ transport activity in vitro. Yet, the evolutionary complexity of MCU proteins, as well as reports about alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 161 publications
(240 reference statements)
1
9
0
Order By: Relevance
“…Although both Arabidopsis MCU1 and MCU2 are sufficient to generate mitochondrial Ca 2+ influx when expressed in yeast, their roles in controlling mtCa 2+ responses in planta had not been established 34,35 . A recent study reported the significantly reduced mtCa 2+ basal level and the mitochondrial Ca 2+ uptake in the root cell of Arabidopsis mcu1 2 3 triple mutant 38 , which matches the expression pattern of MCU1, MCU2 and MCU3 in root cells near the root tip. And the residual Ca 2+ uptake activity in the mcu1 2 3 line is likely due to the predominant expression of MCU6 in roots (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Although both Arabidopsis MCU1 and MCU2 are sufficient to generate mitochondrial Ca 2+ influx when expressed in yeast, their roles in controlling mtCa 2+ responses in planta had not been established 34,35 . A recent study reported the significantly reduced mtCa 2+ basal level and the mitochondrial Ca 2+ uptake in the root cell of Arabidopsis mcu1 2 3 triple mutant 38 , which matches the expression pattern of MCU1, MCU2 and MCU3 in root cells near the root tip. And the residual Ca 2+ uptake activity in the mcu1 2 3 line is likely due to the predominant expression of MCU6 in roots (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Stress stimuli evoke cytosolic Ca 2+ transient and mitochondrial Ca 2+ uptake in plants 16,17,[36][37][38][39][40][41][42] . To study the function of MCUs in the control of mtCa 2+ homeostasis, we generated transgenic Arabidopsis Col-0 lines in which Ca 2+ reporter Aequorin was targeted to mitochondrial matrix under the control of ubiquitin promoter (Col:mtAq).…”
Section: Mitochondrial Ca 2+ Uniporters Are Necessary For Mtca 2+ Hom...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial Ca 2+ ‐ROS crosstalk might be facilitated by the Ca 2+ signalling kinase CIPK9 and VDAC3 in a phosphorylation‐dependent manner. The MCU complex also participates in Ca 2+ uptake at the inner mitochondrial membrane (Ruberti et al, 2022; Wagner et al, 2015; Wang and Teng, 2018). The MCU complex and VDACs act as ROS sensors during hypoxia and inflammation‐mediated oxidative stress in animals (Dong et al, 2017).…”
Section: Organellar Signalling Systemsmentioning
confidence: 99%
“…In plant studies, the bioluminescent protein aequorin (derived from the jellyfish Aequorea victoria ) was first used in 1967 as a genetically encoded Ca 2+ biosensor [ 126 ]. However, despite the use of aequorin to detect Ca 2+ changes in response to various stresses in plants [ 127 ], including temperature [ 128 ], pathogens [ 129 ], salt stress [ 127 ] and wounding [ 130 ] was successful, this system it is not well-suited for real-time imaging due to the extremely low luminescent signal it produces [ 131 ]. Anyway, aequorin-expressing transgenic plants have been used in the study of diverse microbe- or damage-associated molecular patterns (MAMPs/DAMPs) where comparative analyses between the elicitors flg22 and elf18 revealed differences in Ca 2+ signaling and cellobiose exposure which generated an intracellular Ca 2+ elevation [ 129 ].…”
Section: Calcium Imagingmentioning
confidence: 99%